Functional analysis and treatment of self‐injurious feather plucking in a black vulture (Coragyps atratus). Issue 4 (15th September 2019) - Morris, Kristen L.; Slocum, Sarah K.
Abstract : The etiology and maintenance of self‐injurious feather plucking (FP) have been attributed to biological and environmental processes, yet a definitive solution has not been found. The current study investigated the application of a functional analysis and function‐based treatment to reduce the FP of a black vulture ( Coragyps atratus ). FP was found to be maintained by positive reinforcement in the form of contingent attention. A treatment consisting of noncontingent reinforcement decreased FP, and levels of FP remained low during schedule thinning. The current study further demonstrates the validity of function‐based assessment and treatment with captive animals.